METODE DEMONSTRASI DAPAT MENINGKATKAN HASIL BELAJAR SISWA TENTANG BANGUN RUANG SEDERHANA PADA PELAJARAN MATEMATIKA - Haeriyah, Haeriyah (PROSIDING SEMINAR NASIONAL PROGRAM PASCASARJANA UNIVERSITAS PGRI PALEMBANG, 2019)
The problem in this study was the low mathematics learning outcomes of students at SD Negeri 29 Rimau. The purpose of this study was to improve the mathematics learning outcomes of fourth grade students through the application of demonstration methods. The type of research used is Classroom Action Research (CAR) with the stages of each cycle consisting of: planning, implementation, observation, and reflection. This data collection uses observation sheets and formative test questions. Data collection techniques were carried out by non-test techniques and test techniques. This study uses data analysis techniques in the form of qualitative data analysis and quantitative data analysis. The results of the study indicate that the application of demonstration methods can improve mathematics learning outcomes. The percentage of student learning outcomes in the first cycle of